Serological Profiling of Group A Streptococcus Infections in Acute Rheumatic Fever. (26th February 2021) - Lorenz, Natalie; Ho, Timothy K C; McGregor, Reuben; Davies, Mark R; Williamson, Deborah A; Gurney, Jason K; Smeesters, Pierre R; Baker, Michael G; Moreland, Nicole J
Abstract: Rheumatic fever is a serious post-infectious sequela of group A Streptococcus (GAS). Prior GAS exposures were mapped in sera using a large panel of M-type specific peptides. Rheumatic fever patients had serological evidence of significantly more GAS exposures than matched controls suggesting immune priming by repeat infections contributes to pathogenesis.